Mechanical behaviour and microstructure of methane hydrate-bearing sandy sediment observed at various spatial scales - Le Thi Xiu; Bornert Michel; Aimedieu Patrick; Broseta Daniel; Chabot Baptiste; King Andrew; Tang Anh Minh (Science and Technology for Energy Transition, 2024)
Methane hydrates (MHs) are considered an alternative energy resource but also a potential source of geo-hazards and climate change. The physical/mechanical properties of gas hydrate-bearing sandy sediments are strongly dependent on the distribution of hydrates within the pore space. The purpose of this study is to investigate morphologies and pore-habits of MHs formed in sandy sediments by means of experiments that probe a wide range of scales, from the pore scale – using Synchrotron X-Ray Computed Tomography (SXRCT) and optical microscopy – to the core scale, through mechanical property measurements. The same synthetic sands are used, in which MHs are generated successively under excess gas and excess water conditions. At the macroscopic (core) scale, MH pore habits are inferred by comparing the measured sonic wave velocities to velocities calculated from rock physics models and further assessed via triaxial compression tests. Furthermore, Magnetic Resonance Imaging is used to investigate the kinetics of MH formation and distribution along the core height. The pore habits and MH morphologies are directly visualized at the pore (grain) scale by SXRCT and, with still better spatial and temporal resolution, by transmission optical microscopy, revealing some more complex morphologies than in the hydrate pore habits commonly admitted.